City of dreams : a novel [compact disc, unabridged] - Winslow, Don, 1953- (The City Series, 2023)
Danny Ryan, a young widower and mob underboss, has left the East Coast and settled in California with his young son in tow. The move has been good for Danny; in his new base of operations, his power, influence, and wealth have grown. Now he's heading up to Hollywood to rein in two of his crew, who are shaking down a film being made about their involvement in the New England crime war. At the film set, Danny finds himself in a replica of his old neighborhood, standing face-to-face with an actor who's portraying him, and Diane Carson, the actress playing his late wife. Danny is immediately drawn to Diane, but soon learns of a crime in her past that Diane is desperate to cover up. As Danny tries to help Diane, he goes to war against new enemies who don't want him moving in on their West Coast action, and their two worlds pull them in different, dangerous directions.